Simple and robust self-healing technique for millimetre-wave amplifiers - Jia, Haikun; Chi, Baoyong; Kuang, Lixue; Wang, Zhihua (IET circuits, devices & systems, 2016)
A simple and robust self-healing technique for millimetre-wave (mm-wave) amplifiers is proposed. The self-healing technique can correct the operation frequency shifting of the amplifier (including its input and output impedance matching shifting) due to process, voltage, and temperature variations and modelling inaccuracy. A mm-wave amplifier with digitally controlled artificial dielectric transmission lines as fine frequency tuning components and an on-chip power detector as the frequency shifting detector has been implemented in 65 nm complementary metal–oxide–semiconductor to verify the effectiveness of the technique. The operating frequency of five amplifier chips is calibrated by running the self-healing algorithm on a field-programmable gate array development board. On average, the gain of the amplifier is improved by 2.60 dB from 13.66 to 16.26 dB and the input matching is improved by 12.78 dB from −4.89 to −17.67 dB at 56 GHz after the proposed self-healing procedure.